Tamil Film Representation and Real Identity of North Chennai - Silvester, John (Journal of Advanced Research in Journalism & Mass Communication, 2023)
The article explores the similarities and differences between the representation in Tamil films and the real life of North Chennai people and the impacts it created on the people both the inhabitants as well as the people outside North Chennai. The study also aimed to analyse how the film has impacted building Identity in the present generation. The researcher has taken 3 films that have been identified by the people who were interviewed. They are namely Puthupettai(2006) Directed by K. Selvaraghavan Vada Chennai (2018) Directed by Vetrimaaran and Madras Directed by Pa. Ranjith. These 3 directors’ projections of North Chennai have impacted people and identified the people easily. Portraying North Chennai is not new to Tamil Cinema. There was a completely negative portrayal now it has gradually changed and apparently, a sense of positivity has begun to spread among the people. The study analysed the names and the philosophy behind them, economic conditions and migrations, the social system, cultural transformations and games and their values projected. How to cite this article: Silvester J. Tamil Film Representation and Real Identity of North Chennai. J Adv Res Jrnl Mass Comm 2023; 10(1): 24-28. DOI: https://doi.org/10.24321/2395.3810.202305